2021
DOI: 10.4102/sajhrm.v19i0.1564
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of employee empowerment on turnover intention in a mining organisation

Abstract: Orientation: Mining plays a significant role in the South African economy and is crucial for job creation opportunities. Mining organisations are plagued by various challenges, which include turnover intention.Research purpose: The current study sought to establish whether employee empowerment (psychological and structural empowerment) predicts turnover intention in a mining organisation.Research approach/design and method: The study followed a quantitative research approach and used a cross-sectional design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…High performing employees are usually more satisfied with their jobs (Mahmood & Sahar, 2017). Empowerment influences job satisfaction (Ngqeza & Dhanpat, 2021), and employees can use informal skills to influence managers to make appropriate decisions for specific service situations. informal skills can help workers learn the language (Eriksson & Engstrom, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…High performing employees are usually more satisfied with their jobs (Mahmood & Sahar, 2017). Empowerment influences job satisfaction (Ngqeza & Dhanpat, 2021), and employees can use informal skills to influence managers to make appropriate decisions for specific service situations. informal skills can help workers learn the language (Eriksson & Engstrom, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceptions of formal and informal skills can influence access to organizational empowerment structures, and a combination of formal power, informal power, and access to empowerment structures can predict the level of employee involvement in workrelated decisions. Empowerment programs significantly affect employee performance (Eriksson & Engstrom, 2018;Ngqeza & Dhanpat, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Yesufu (2020) and Beijer et al (2021), different organisations apply HR practices before and after recruiting an employee. The pre-recruitment practices include communication, recruitment and selection, compensation and benefits, whilst the practices after recruitment include training, development, empowerment, compensation and benefits (Modau, Dhanpat, Lugisani, Mabojane, & Phiri, 2018;Ngqeza & Dhanpat, 2021;Yesufu, 2020). Kumudha and Harsha (2016) in their study on the relationship between HR practices and employee retention in a private hospital in the UAE found that the lack of organisational commitment impacts employees' perceptions and sense of belonging to an organisation as most of these employees are unable to relate their career growth to the organisation's path and are dissatisfied with the practices of HR policies.…”
Section: Employee Retentionmentioning
confidence: 99%